Measles Antibody Level In Unvaccinated Underfive Children Of Himachal Pradesh - Bhardwaj A.K; Gupta B.P; Sood D.K; Ahluwalia S.K; Vaidya N.K (Wolters Kluwer Medknow Publications, 1992)
Serological survey of unvaccinated under-five children was undertaken in three different areas in the State of Himachal Pradesh. Seropositivity rate of 82.4% at 3 months of age, decreased to a level of 12.6% in the age group of 9 to 12 months. There was a gradual decrease in seropositivity during infancy with an increase after the age of one year. No significant difference between the three areas was found. With increasing levels of malnutrition the seropositivity decreased.